2021
DOI: 10.1002/anie.202102833
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Tracking and Dynamically Quantifying of Reversible Changes of Extracellular Ca2+ in Multiple Brain Regions of Freely Moving Animals

Abstract: Understanding physiological and pathological processes in the brain requires tracking the reversible changes in chemical signals with long‐term stability. We developed a new anti‐biofouling microfiber array to real‐time quantify extracellular Ca2+ concentrations together with neuron activity across many regions in the mammalian brain for 60 days, in which the signal degradation was < ca. 8 %. The microarray with high tempo‐spatial resolution (ca. 10 μm, ca. 1.3 s) was implanted into 7 brain regions of free‐mov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(67 citation statements)
references
References 48 publications
0
66
0
1
Order By: Relevance
“…It is important to verify that the pH response is not influenced by protein adsorption, which is abundant in rat brains or whole blood, , so the anti-biofouling ability of the present biosensor was examined. Here, albumin from bovine serum albumin (BSA), which acts as a model molecule, was studied with the same experimental procedures in this work.…”
Section: Results and Discussionmentioning
confidence: 99%
“…It is important to verify that the pH response is not influenced by protein adsorption, which is abundant in rat brains or whole blood, , so the anti-biofouling ability of the present biosensor was examined. Here, albumin from bovine serum albumin (BSA), which acts as a model molecule, was studied with the same experimental procedures in this work.…”
Section: Results and Discussionmentioning
confidence: 99%
“…[2c] However, in the neurons, no significant changes were observed in size and frequency of mitochondrial CaPP during hypoxia (Figure 4i). On the other hand, extracellular Ca 2 + was simultaneously measured by using our previously developed method, [6] it was observed that extracellular Ca 2 + was decreased from 1.24 � 0.06 mM to 0.58 � 0.05 mM in hippocampus of WT mice brain upon acute hypoxia for 60 min, while that of Ca 2 + mito was increased by � 0.27 mM. Meanwhile, extracellular Ca 2 + was decreased only by � 0.06 mM in that of ASIC1a À /À mice (Figure 4j).…”
Section: Forschungsartikelmentioning
confidence: 99%
“…[5] Recently, we developed an electrochemophysiological microarray with excellent anti-pollution performance for real-time mapping and quantification of ion signals in the deep brain of a freely moving mouse. [6] Fluorescence imaging combined with fiber photometry and modern genetic tools, have revolutionized neuroscience by recording of intracellular molecular signals in living animals. [7] To date, most of these fluorescent approaches study brain activity mainly by recording the changes of Ca 2 + signal, [8] simultaneously recording of different neurochemical signals is still challenging due to the broad fluorescence peaks.…”
Section: Introductionmentioning
confidence: 99%
“…3.1 体外分析 生理活性分子, 如小分子 [68,27] 、核酸 [69,70] 、蛋白 质 [71,72] 等在生命活动过程中扮演着重要的角色, 其 选择性分析对于了解生命活动过程的化学本质具有 重要意义. 近些年来, 利用核酸适体电化学传感器实 现了体外及细胞层次生理活性分子定性和定量分析 [73][74][75] .…”
Section: 核酸适体传感器的应用unclassified